Evaluación morfométrica y medición de longitud en vellosidades intestinales en pollos de engorde de la línea Ross 500 suplementados con ajo (allium sativum) a diferentes dosis en el concentrado comercial en el municipio de Popayán. (2023)
The aim of this research was to evaluate the effect of garlic supplementation in commercial feed on 128 Ross 500 broiler chickens as a potential alternative to growth promoters in broiler chickens. Garlic contains compounds that promote animal health and optimize their well-being. To achieve this, the chickens were evaluated from the first day of age, and it was observed if there was an improvement in weight gain and an increase in intestinal villi length and width. Garlic was added to commercial feed up to 42 days of production, using a random system from day 16 to 42. An analysis of variance, ANOVA test, and comparisons were applied to evaluate the results. The poultry industry has expanded in recent years to meet the growing demand for poultry products, so producers are seeking to improve the quality of meat and feed conversion of birds to increase their performance and meet market demand. The chickens were divided into different groups, each receiving a different dose of garlic in their commercial concentrate. The length of the chickens' intestinal villi was measured, and a morphometric evaluation was performed to determine changes in the structure and shape of the villi.